Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Soal PISA di Kelas IX-F SMP Negeri 1 Bukitiinggi - Aprilia, Riski Sakinah; Firmanti, Pipit; Tasnim Rahmat; Rusdi, Rusdi (Indo-MathEdu Intellectuals Journal, 2024)
This research is motivated by the results of observations, where students are not used to solving critical thinking problems, especially PISA questions. This study aims to describe students' critical thinking skills in solving PISA questions. This type of research is a type of quantitative descriptive research. The sample in this study is 30 students of Class IX-F SMP Negeri 1 Bukittinggi. The data collection technique used is a test of critical thinking skills in PISA questions. The collected data is analyzed by the procedure of analyzing the results of the work, presenting the data and drawing conclusions. The results of the data analysis showed that students' critical thinking skills in solving PISA questions in class IX-F SMP Negeri 1 Bukittinggi as a whole were classified in the low category with a percentage of 52.6% and different for each indicator. This can be seen in the completion of students' pisa questions on 4 indicators of critical thinking ability, namely Interpretation is 67% in the high category, for the Analysis, Evaluation and Inference indicators are classified in the low category with 56.44%, 43.83% and 45.16% respectively. So it is concluded that the level of students' critical thinking ability in solving PISA questions in class IX-F SMP Negeri 1 Bukittinggi is classified as low